Succession disputes on the Armenian Throne: considerations on the political relations between Romans and Parthians in Tacitus (Annals, VI, 31-37) - da Costa Campos, Rafael (Romanitas - Revista de Estudos Grecolatinos, 2025)
This article examines a passage from Tacitus’ Annals, offering a concise account of a military conflict in the Roman East. Armenian, Parthian, and Roman auxiliary forces clashed amid succession disputes involving Armenians, Parthians, and Romans. Tacitus analyzes the event, shedding light on the challenges of Emperor Tiberius’ foreign policy and on the Julio-Claudian dynasty’s interactions with client kingdoms and foreign adversaries. Moreover, the passage offers insights into Roman perceptions of neighboring and frontier peoples. Finally, it highlights historical shifts in Roman imperialist perspectives during the transition from Republic to Principate.